Assessment of Canine Pancreas‐Specific Lipase and Outcomes in Dogs with Hemodialysis‐Dependent Acute Kidney Injury. (22nd February 2018) - Takada, K.; Palm, C.A.; Epstein, S.E.; Cowgill, L.D.
Abstract : Background: Renal replacement therapies can be life‐saving for dogs with severe acute kidney injury (AKI), however, comorbidities including pancreatitis might affect outcome. Hypothesis/Objectives: To investigate the prevalence of pancreas‐specific lipase (Spec cPL) measurements consistent with pancreatitis (≥400 μg/L) in dogs undergoing intermittent hemodialysis (IHD) for treatment of AKI and to determine whether there were associations between 30‐days outcomes and Spec cPL measurements. Animals: Fifty‐three client‐owned dogs presented to teaching hospitals between November 2008 and September 2016 that underwent IHD. Methods: Retrospective medical record review from dogs that received IHD for management of AKI and also had a Spec cPL measurement. Association between survival, dialysis‐dependency, and Spec cPL measurements was assessed. Results: Forty of 53 (76%) dogs were alive at 30‐days and 33/53(62%) had a Spec cPL result ≥400 μg/L. Spec cPL was not significantly different either between surviving (635.5 μg/L, range 29–1, 001) and nonsurviving dogs (860 μg/L, range 56–1, 001; P  = 0.75) or between dialysis‐dependent (1, 001 μg/L, range 177–1, 001) and nondialysis‐dependent dogs (520 μg/L, range 29–1, 001; P  = 0.08). Spec cPL ≥400 μg/L was not significantly associated either with survival ( P  = 0.74) or dialysis‐dependency ( P  = 0.33). Conclusions and Clinical Importance: Results revealed a high prevalence of Spec cPL ≥400 μg/L in dogs with AKI treated with IHD. No significant associations between Spec cPL and survival or dialysis‐dependency in dogs with AKI at 30 days were identified in the current study, however, the latter could be due to lack of power in this study.